Pendidikan Kesehatan Pencegahan Hipertensi - Aris Widiyanto; Joko Tri Atmojo; Asruria Sani Fajriah; Santy Irene Putri; Prima Soultoni Akbar (Poltekkes Kemenkes Surakarta, 2020)
Background: The prevalence of Hypertension is increasing and increasingly worrying so that Hypertension is still a global problem. One way to be able to prevent Hypertension by controlling its risky behaviors, including by avoiding smoking, unhealthy diet (lack of consumption of vegetables and fruits as well as consumption of sugar, salt and excess fat), preventing the occurrence of obesity, lack of physical activity, excessive alcohol consumption and stress. One of the top priorities and one of the effective nursing interventions to increase the level of public awareness is the existence of health education programs. After participating in health education activities, it is expected that the public can know and be able to prevent the onset of hypertension. Methods: Health Education is carried out by means of lectures and discussions with the community, using LCD media accompanied by leafleat distribution and held on December 24, 2019 with the target of all citizens in tawangsari village, Mojosongo Village, Jebres District. Results: Implementation of hypertension prevention health education followed by 20 participants. The activity went smoothly, the participants were enthusiastic and able to understand the material delivered where when the presenter evaluated the participants were able to answer well in accordance with the questions asked. Conclusion: hypertension prevention health education activities effectively open insights into the health knowledge of citizens, the creation of public awareness to implement a healthy lifestyle, check blood pressure regularly, and routinely consume hypertensive drugs.